Collegiate women`s wrestling body fat percentage and minimum wrestling weight values: Time for revisiting minimal body fat percent? - Jagim, A. R.; Tinsley, G. M.; Oppliger, R. A.; Horswill, C. A.; Dobbs, W. C.; Fields, J. B.; Cushard, C.; Rademacher, P. D.; Jones, M. T. (Journal of the International Society of Sports Nutrition, 2024)
Background The estimation of body fat percentage (BF%) in wrestling is used to determine the minimum wrestling weight (MWW) and lowest allowable weight class (MWC) in which wrestlers are eligible to compete. A 12% minimum threshold is currently used for women wrestlers, yet a potential increase for safety has been discussed. Because of the novelty of collegiate women`s wrestling, there is a paucity of literature available on the body composition norms of this population. The purpose of this study was to provide a descriptive summary of BF% and MWW values of female wrestlers and how MWW values would change with the use of different BF% thresholds.